2022
DOI: 10.3390/coatings12050658
|View full text |Cite
|
Sign up to set email alerts
|

Research on Film-Forming Characteristics and Mechanism of Painting V-Shaped Surfaces

Abstract: Painting a V-shaped surface, which is widely found in various facilities and equipment, often results in poor coating quality, which may be caused by an insufficient understanding of film-forming characteristics and mechanism. In this study, computational fluid dynamic (CFD) simulations were carried out for in-depth research on the film-forming characteristics and mechanism of painting V-shaped surfaces. The mathematical model of film formation was established with the Euler–Euler method, and the unstructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ye et al [108] carried out a numerical simulation of spray film formation with variable gun pressure on a right-angled slot surface of a car body. Chen et al [109,110] also studied the film formation characteristics of V-shaped surface spraying with different connecting angles based on the VOF model, and the simulation results obtained were in good agreement with the coating thickness obtained from the experiments.…”
Section: Numerical Simulations Of Film Formation Characteristics On C...mentioning
confidence: 63%
“…Ye et al [108] carried out a numerical simulation of spray film formation with variable gun pressure on a right-angled slot surface of a car body. Chen et al [109,110] also studied the film formation characteristics of V-shaped surface spraying with different connecting angles based on the VOF model, and the simulation results obtained were in good agreement with the coating thickness obtained from the experiments.…”
Section: Numerical Simulations Of Film Formation Characteristics On C...mentioning
confidence: 63%
“…The results produce a straight line in the increasing region using regression analysis. The relationship can be expressed approximately as θ = −100.24 + 20.52 ln γ (19) Coatings 2024, 14, 282 8 of 23 In case II, the AoR trends to zero with decreasing wall-paint droplet surface energy in the moderating region. A droplet layer is formed, representing a droplet film on the flat plate.…”
Section: Virtual Calibration Test Of Surface Energymentioning
confidence: 99%
“…The predicted droplet diameter distribution using OpenFOAM code was compared to experimental data in the spray atomization. The formation of coating film was modeled using the Euler-Euler approach in the static spraying and dynamic spraying processes [19]. The film formation and thickness distribution were predicted in a V-shaped surface with an air cap of a spray gun.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al [22] discovered a correlation between droplet particle size distribution and atomization air volume as well as forming air volume. Chen et al [23] investigated the distribution of V-shaped surface coatings and observed a bimodal distribution in coating thickness. Chen et al [24] conducted research indicating that the coating thickness of the arc section is greater than that of the plane section.…”
Section: Introductionmentioning
confidence: 99%